Sunlight-driven simultaneous CO2 reduction and water oxidation using indium-organic framework heterostructures - Zhongjie Cai; Hongwei Liu; Jiajun Dai; Bao Li; Liming Yang; Jingyu Wang; Huaiyong Zhu (Nature Communications)
Abstract Overall artificial photosynthesis, as a promising approach for sunlight-driven CO2 recycling, requires photocatalysts with efficient light adsorption and separate active sites for coupling with H2O oxidation. Here we show a In-based metal–organic framework (MOF) heterostructure, i.e., In-porphyrin (In-TCPP) nanosheets enveloping an In-NH2-MIL-68 (M68N) core, via a facile one-pot synthesis that utilises competitive nucleation and growth of two organic linkers with In nodes. The coherent interfaces of the core@shell MOFs assure the structural stability of heterostructure, which will function as heterojunctions to facilitate the efficient transfer of photogenerated charge for overall photosynthesis. The In-TCPP shell in MOFs heterostructure improves CO2 adsorption capabilities and visible light absorption to enhance the photocatalytic CO2 reduction. Simultaneously, In-O sites in M68N core efficiently catalyze H2O oxidation, achieving high yields of HCOOH (397.5 μmol g−1 h−1) and H2O2 (321.2 μmol g−1 h−1) under focused sunlight irradiation. The superior performance of this heterostructure in overall photosynthesis, coupled with its straightforward synthesis, shows great potential for mitigating carbon emissions and producing valuable chemicals using solar energy.